2022
DOI: 10.1021/acs.jpcc.1c10726
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study of Optically Controlled Phase Change Materials

Abstract: The optically controlled phase change technology makes the phase change material produce an obvious energy barrier between a solid and a liquid, which can effectively prevent spontaneous heat loss. Based on the molecular dynamics method, the microscopic model of the optically controlled composite system (capric acid/4-(phenyldiazenyl)phenyl decanoate) was established and the simulation of the AZO trans−cis isomerization process was based on the modification of the dihedral angle parameters of AZO in the conden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 67 publications
(103 reference statements)
0
6
0
Order By: Relevance
“…In addition, it was found that the chain length and side chain density of the polymer also have an effect on the thermal conductivity. Wang et al 174 investigated the physical properties and temperature differences during the isomerization process of phase change materials doped with Azo. As shown in Fig.…”
Section: Application In Most Systemsmentioning
confidence: 99%
“…In addition, it was found that the chain length and side chain density of the polymer also have an effect on the thermal conductivity. Wang et al 174 investigated the physical properties and temperature differences during the isomerization process of phase change materials doped with Azo. As shown in Fig.…”
Section: Application In Most Systemsmentioning
confidence: 99%
“…60 The thermal conductivity 111 and solubility 56 of the materials are also changed along with the liquefaction process, which is mainly caused by the isomerization leading to the reduction of the degree of symmetry order or the change in polarity. 115 The solid to liquid phase transition of small molecule azo crystals or azopolymers could also be utilized in switching of gas adsorption, 54 nanowetting, 149 and emission-switchable fluorescence. 150 through the phase transition process (Figure 22).…”
Section: Properties and Applications Of Optmsmentioning
confidence: 99%
“…In addition, if their crystallization points are higher than room temperature, the problem of spontaneous heat loss after charging is serious, which can be optimized by combining the azo solid–liquid OPTMs and the organic PCMs, to simultaneously store the photon energy and ambient thermal energy. Such an elegant combination strategy leads to a win–win situation . As shown in Figure a, Han et al introduced azo compounds into an organic PCM (tridecanoic acid) in the form of dopants. , To ensure a sufficiently high miscibility, the azo compound was functionalized with a tridecanoic ester group.…”
Section: Designs and Phase Change Mechanisms Of Optmsmentioning
confidence: 99%
See 2 more Smart Citations